Factors affecting employee retention at Pulai Springs Resort / Afifah Nabilah Kamaruzaman - Kamaruzaman, Afifah Nabilah (Faculty of Business and Management, 2019)
The purpose of the research is to identify whether training and development programs, compensation plans, working environment and leadership styles factor were related in influencing employee retention at Pulai Springs Resort. The data was collected among 150 from 248 employees in all the department from this organization. Simple random sampling technique has been used as a sampling technique. The data collected then key in using SPSS (Statistical Package for Social Science) to analyse all the data gathered through the questionnaire. Several analysis have been done by using the SPSS such as reliability analysis, frequency distribution, descriptive and multiple regression. Based on the data obtained, all the independent variables (training and development programs, compensation plans, working environment) is significance toward employee retention at Pulai Springs Resort. This indicated that the independent variable and dependent variable move in the same direction as one variable increase the other variables also.